Potential application of novel technology developed for instant decontamination of personal protective equipment before the doffing step - Mascarenhas, Luís Alberto Brêda (2021)
Centro Universitário SENAI CIMATEC. Instituto SENAI de Sistemas Avançados de Saúde. Salvador, BA, Brasil.